Study protocol for a hybrid implementation-effectiveness trial of Game Changers for Cervical Cancer Prevention in Uganda - Glenn J. Wagner; Laura M. Bogart; Joseph K. B. Matovu; Violet Gwokyalya; Jolly Beyeza-Kashesya; Allison Ober; Harold D. Green; Sylvia Nakami; Margrethe Juncker; Eve Namisango; Emmanuel Luyirika; Ryan K. McBain; et al. (PLoS ONE, 2025)
Introduction Cervical cancer (CC) is the leading cause of cancer-related deaths among Uganda women, yet rates of CC screening are very low. Training women who have recently screened to engage in advocacy for screening among women in their social network is a network-based strategy for promoting information dissemination and CC screening uptake. Methods Drawing on the Exploration, Preparation, Implementation and Sustainment (EPIS) framework for implementation science, this hybrid type 1 randomized controlled trial (RCT) of a peer-led, group advocacy training intervention, Game Changers for Cervical Cancer Prevention (GC-CCP), will examine efficacy for increasing CC screening uptake as well as how it can be implemented and sustained in diverse clinic settings. In the Preparation phase we will prepare the four study clinics for implementation of GC-CCP and the expected increase in demand for CC screening, by using qualitative methods (stakeholder interviews and client focus groups) to identify and address structural barriers to easy access to CC screening. In the Implementation phase, GC-CCP will be implemented over 36 months at each clinic, with screened women (index participants) enrolled as research participants receiving the intervention in the first 6 months as part of a parallel group RCT overseen by the research study team to evaluate efficacy for CC screening uptake among their enrolled social network members. All research participants will be assessed at baseline and months 6 and 12. Intervention implementation and supervision will then be transitioned to clinic staff and offered as part of usual care in the subsequent 30 months as part of the Sustainability phase. Using the RE-AIM framework, we will evaluate engagement in GC-CCP and CC advocacy (reach), alter CC screening (effectiveness), adoption into clinic operations, implementation outcomes (acceptability, feasibility, fidelity, cost-effectiveness) and maintenance. Discussion This is one of the first studies to use a network-driven approach and empowerment of CC screened peers as change agents to increase CC screening. If shown to be an effective and sustainable implementation strategy for promoting CC screening, this peer advocacy model could be applied to other preventative health behaviors and disease contexts. Trial registration NIH Clinical Trial Registry NCT06010160 (clinicaltrials.gov; date: 8/17/2023).